Review of Peter Szendy. 2008. Listen: A History of Our Ears. Translated by Charlotte Mandell. New York: Fordham University Press - Kane, Brian (Current Musicology, 2008)
Peter Szendy’s first translation into English has appeared on the shelves not merely by chance. It arrives in the wake of two recent trends in the academic world: an intense interest in all things having to do with the history and culture of the senses, and the sudden accession of Jean-Luc Nancy as the Academy’s ‘philosophe du jour’. Of course, these two trends are not unrelated, for few philosophers have questioned the senses, especially the sense of touch, that Nancy has over the past two decades. However unlike the terse, Heideggerian-inflected prose of Nancy, Szendy’s work appears far more sober. At first glance, it is little more than a piecemeal work, centered around three topics: a sketchy history of musical copyright, a rehashing of the rise of the work concept, and another critique of “structural listening” in the name of the Benjamin distraction.